If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -1b + -4(5a + -7b + 8c) = 0 4a + -1b + (5a * -4 + -7b * -4 + 8c * -4) = 0 4a + -1b + (-20a + 28b + -32c) = 0 Reorder the terms: 4a + -20a + -1b + 28b + -32c = 0 Combine like terms: 4a + -20a = -16a -16a + -1b + 28b + -32c = 0 Combine like terms: -1b + 28b = 27b -16a + 27b + -32c = 0 Solving -16a + 27b + -32c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-27b' to each side of the equation. -16a + 27b + -27b + -32c = 0 + -27b Combine like terms: 27b + -27b = 0 -16a + 0 + -32c = 0 + -27b -16a + -32c = 0 + -27b Remove the zero: -16a + -32c = -27b Add '32c' to each side of the equation. -16a + -32c + 32c = -27b + 32c Combine like terms: -32c + 32c = 0 -16a + 0 = -27b + 32c -16a = -27b + 32c Divide each side by '-16'. a = 1.6875b + -2c Simplifying a = 1.6875b + -2c
| -2(5+3b)-2(6b-7)=40 | | s+3.5s+10=64 | | 5(3w-2)-7=18 | | x^2+3x+2x=6 | | x^2=4x-29 | | 6n+3n+14=0 | | x^2-24x-80=0 | | 14-(x+9)=6x-2 | | x^2-18x-175=0 | | 5e+14=12e-42 | | 8.666666667+y=y^2 | | 8k+13=-8+4+10k+3 | | x+8x+15=0 | | (X^2)-14X-147=0 | | 10(2b+c-6a)-8(a-7c+8b)= | | 5+3(a-4)=2(a+1) | | 10d-27=6d+9 | | 3a-7b-1(4a-3b)= | | 4(x-2)+3=6x-11 | | 4a+3a+5b= | | 2(x-4)+2x=4x+1 | | 4m+8=-10+7m | | 8+(4-.5w)3=8 | | 224988/12=x/1 | | 5r=-r+6 | | 7m-(m-9)=39 | | 4.5+2z=2z^2 | | 4c+5=7c-13 | | -12=-4+5x+3x | | .7x+5=19 | | 6x-(3x-5)-3=6-(8-x) | | -9+4j=-5j |